Orthophosphate uptake in proteoid roots of naturally occurring Hakea sericea Schrad. - Sousa, M. F. (2004)
Poster apresentado no congresso "14th Congress of the Federation of European Societies of Plant Biology", August 23-27, 2004, Cracow, Poland.